Comparison of volatile compounds in different parts of fresh Amomum villosum Lour. from different geographical areas using cryogenic grinding combined HS-SPME-GC-MS - Ling-Xiao Chen; Yun-Feng Lai; Wei-Xiong Zhang; Jing Cai; Hao Hu; Ying Wang; Jing Zhao; Shao-Ping Li (BMC, 2020)
Abstract Background The essential oil is one of the main active ingredients of Amomum villosum Lour. However, volatile compounds are easily lost during the drying, storage and even sample preparation procedure. Therefore, using fresh samples can obtain more accurately data for qualitative and comparative analysis. Methods In this study, the volatile compounds in different parts of fresh A. villosum from different origins were systemic analyzed and compared by using cryogenic grinding combined HS-SPME-GC-MS for the first time. GC-MS analyses were performed on a 6890 Series GC instrument coupled to a 5973 N mass spectrometer. The volatile compounds were extracted by the SPME fiber (100 μm PDMS). Analytes separation was achieved on a HP-5MS capillary column. The oven temperature was initially programmed at 70 °C, then raised 4 °C/min to reach 125 °C and then programmed at 0.5 °C/min to 133 °C, then at 6 °C/min to 170 °C and finally, at 20 °C/min to 280 °C held for 2 min. The temperatures of the injection port, ion source and transfer line were set at 250 °C, 230 °C and 280 °C, respectively. Results Forty-eight main compounds were identified in different parts of fresh A. villosum. The most abundant components in fresh fruit samples were camphor (3.91%), bornyl acetate (10.53%), caryophyllene (8.70%), β-bisabolene (11.50%), (E)-nerolidol (14.82%) and cubenol (10.04%). This is quite different with that of dried samples analyzed in our previous work. As different parts of the same plant, many common components with biological activities were detected in fruit and other parts. In principle components analysis (PCA) and hierarchical clustering analysis (HCA), four parts of A. villosum were divided into different groups clearly. Additionally, fruit and root samples also could be divided into two subgroups (HCA) in accordance with their regions. Conclusion The developed method was successfully used for qualitative and comparative analysis of volatile compounds in fresh A. villosum samples. Additionally, using fresh samples can obtain much more information which is helpful for their performance in the fields of functional foods, agriculture and biomedical industry. Furthermore, our research is helpful for comprehensive utilization and quality control of A. villosum.